Musical Parody of Acapella Mataraman: A Creativity Compromise for the Performing Arts Market in Yogyakarta - Firmansah Firmansah (Graduate School of Institut Seni Indonesia Yogyakarta, 2017)
This study aims to identify and understand the creative process of artists in the performing arts market. The concept of creativity is often the response of the high degree of creativity. Basically an assumption appears if the artist is able to survive in the market is the result of creativity in the performing arts is a form of alternative or compromise. This phenomenon occurred in the group Acapella Mataraman. This case study is based on the concept of Jennifer Lindsay and Umar Kayam about the existence of performing arts groups. The primary data are gained from the interview process with Pardiman Djoyonegoro, then, it is completed with the secondary data through a focus group discussion to explore deeper about creativity process on Acapella Mataraman. The results show that the repertoire of pangkur jenggleng and emperan Nuswantara is a form of compromise. Musical sounds and rhythms of modern music elaborated and presented through acapella techniques. Supplemented by the concept of parody that has appeal and value to the consumer tastes of the performing arts. This form is an effective medium for the delivery of criticism and moral content on each of the repertoire.